Mobile-assisted language learning using Gamification and Virtual Reality techniques during the COVID-19 pandemic (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
During the global pandemic in Guayaquil, Ecuador, and the accelerated transition to online education, teachers questioned the integration of educational technology in the training of technology scholars and its impact on the learning process. The main objectives of this study were to understand the contextual perception of the scholars on the use of technologies such as Mobile Device Assisted Language Learning, Gamification and Virtual Reality in teaching English to higher technology students during the COVID-19 pandemic in Guayaquil. In addition, we sought to identify which of these technologies teachers preferred to use to teach English. This study followed a quantitative approach and used an adapted online questionnaire. The results of the reliability test showed high consistency with a value of 0.866 according to Cronbach's Alpha statistic.